(3EOGQI GdLhOI aj GdefXeGJ GdeJejRI (B/s - (3MehO, NVjQ cGXes; (3GdTjN, QhGf efjQ s ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eaghe GdLhOI GdTGedI ceONd dGOGQI GdLhOI , GdGOGQI GdGSJQGJjLjI (B: (3GdJNWjW h GdJfajP ddMUhd Ydi GdejRI GdJfGaSjI , KbGaI GdLhOI , QVGdA GdeSJgdcjf h GdGMJaGX Hge , Jecjf GdYGedjf , GdbjGOI h GdZjjQ, HfGA GdaQb h aQb GdYed , GdGJUGd GdaYGd , GdJOQjH h GdJYdje , GOGQI GdUQGY , GJNGP GdbQGQGJ h Md GdeTcdGJ , GdJMSjf GdeSJeQ h GdebGQHI GdeQLYjI , COhGJ GdLhOI GdTGedI(B.s
(3eQGLY U(B.315s
Keywords: (3GdEjRhs; (3GdLhOIs; (3GdLhOI `` GOGQIs; (3GdefXeGJs; (3VHW GdLhOIs